The Relationship Between Caring Pediatric Nurses and The Level of Satisfaction of Parents of Patients at Inpatient Ward PKIA - Dina Novenda Sari; Endah Dessirya; Mustaqimah Mustaqimah; Rusana Rusana; Dewi Rezeki; Erlin Fitria Yusliana (Indonesian Journal of Global Health Research, 2024)
Patient satisfaction is a reflection of the quality of health services. Caring behavior toward patients is the essence of nursing, and it can positively contribute to patient satisfaction in receiving nursing services. Caring for patients in the pediatric ward is very important so they can feel more comfortable during their treatment. This study aims to determine the relationship between caring pediatric nurses and the level of parental satisfaction and to determine the characteristics that most influence the satisfaction of parents of patients at RSUPN Dr. Cipto Mangunkusumo Jakarta. This descriptive correlation study uses a cross-sectional approach involving 113 parents of patients in the pediatric inpatient ward at Dr. Cipto Mangunkusumo Hospital, Jakarta. The instruments used were the CBI-24 (Caring Behavior Inventory-24) questionnaire and the PSNCQQ (Pediatric Short-Form Neurological Care Quality Questionnaire). The results of the univariate analysis show a high caring rate of 58.41% and a low caring rate of 41.59%. The description of patient satisfaction shows 58.41% satisfied and 41.59% dissatisfied. The results of the bivariate analysis using the chi-square test obtained a p-value of <0.001 (OR 95% CI (0.165; 0.072-0.377)), which indicates a significant relationship between caring nurses perceived by patients and the satisfaction of the pediatric patient's parents. These results recommend evaluating the performance of nurses’ communication, formal and informal education, and motivating caring behavior to create a higher quality and patient-centered health service environment.